Pendampingan Penyusunan Perencanaan Strategis Wilayah Berbasis Partisipasi Berdasarkan Potensi dan Kerentanan Wilayah Pesisir Kelurahan Pesawahan Kota Bandar Lampung - Aulia Rahmawati; Fritz Akhmad Nuzir; Kustiani Kustiani; Aditya Mahatidanar; Okta Ainita; M Denu Poyo (Yayasan Inspirasi El Burhani, 2026)
Introduction: Urban coastal areas possess significant development potential but also face various development challenges. Pesawahan Village, Bandar Lampung City, is one of the coastal areas that has considerable local economic potential, strong social capital, and opportunities for community-based tourism development. However, environmental, social, and economic problems remain major obstacles to achieving sustainable regional development. Community involvement in the development planning process is essential to ensure that development programs are formulated in accordance with local needs and regional characteristics Objective: This community service program aimed to enhance community capacity in preparing participatory strategic regional planning by integrating the potentials and vulnerabilities of coastal areas as the basis for determining development priorities in Pesawahan Village, Bandar Lampung City. Method: The community service activities were carried out using a participatory approach through field observations, Focus Group Discussions (FGDs), participatory mapping, training sessions, and community mentoring. Result: The assistance program successfully identified the existing conditions of the study area, including environmental infrastructure issues, tidal flood vulnerability, local economic potential, tourism potential, and the capacity of community institutions. Through Focus Group Discussions (FGDs) and participatory mapping, community members successfully developed maps of regional potentials and vulnerabilities, which served as the basis for preparing the strategic regional planning document. In addition, the community formulated several development priorities, including drainage improvement, environmental enhancement, the development of UMKM, and community-based tourism development. These outputs were compiled into a participatory regional action plan document containing analyses of local potentials, regional vulnerabilities, and development priorities, which serves as a reference for sustainable development in the coastal area. Conclusion: Assistance in the preparation of participatory strategic regional planning was effective in enhancing community capacity and participation in local development planning processes. The integration of regional potential identification, coastal vulnerability analysis, and participatory action plan formulation contributed to the development of planning directions that better reflect community needs. Furthermore, the program strengthened community commitment to supporting inclusive, adaptive, and sustainable development in coastal areas.